Study of Political impact on Post-Colonialism in Kazuo Ishiguro’sRemains of the Day - TSURHO, ROKOZOLIE; PRASAD, SANJAY (International Journal of Psychosocial Rehabilitation, 2021)
The Remains of the Day by Kazuo Ishiguro is a British-American drama known for winning the Man Booker Prize in 1989 and the Nobel Prize in Literature in 2017.It is written in the backdrop of the World War I scenario in England and revolves around the duty of professionalism portrayed through the character of Mr. Stevens serving as a steward in the house of Darlington Hall. It is a recollection on the horrors of war and the politics played in the ascent of Fascism. The present paper is an attempt to explore the impacts of politics on society in the novel.